The marketing information system of the tourism enterprise - Kravtsov, Sergiy (My University, 2017)
The article is devoted to the research of the essence and the structure of the marketing information system of tourism enterprise. A current state of the marketing information system of tour operators and tour agents in Ukraine is analyzed. The schematic for improvement of marketing information system of Ukrainian tourist enterprises is created.
Keywords: marketing information system; travel company; tour operator; маркетингово-інформаційна система; туристична компанія; туроператор; кафедра туристичного та готельного бізнесу; маркетингово-информационная система; туристическая компания; туроператор